Changes in natural disaster risk: Macroeconomic responses in selected Latin American countries - Marlène Isoré (Economies, 2018)
This paper studies the theoretical effects of changes in disaster risk on macroeconomic variables in five Latin American economies. It compares country-specific variants of the New Keynesian model with disaster risk developed by Isoré and Szczerbowicz (2017). Countries with higher price flexibility, such as Argentina, Brazil, and Mexico, are found to be relatively less vulnerable to disaster risk shocks, as compared to Chile and Colombia in particular. Overall, the analysis suggests that increases in the probability of natural disasters over time may have significant macroeconomic effects, beyond the direct impact of actual disaster occurrences themselves.
Keywords: E20; E31; E32; Q54; 330; natural disasters; disaster risk; DSGE models; business cycles; Latin America